Walking Classroom Nourishes Hearts, Food Education Forges New Talents ——A Holistic Original Food Education Practice at Ning’an Korean Ethnic Minority Primary School (Including Kindergarten Division) - Ji Jin; Min Zeng (Education Research on Study Tours and Practice, 2026)
Food education serves as a comprehensive carrier integrating labor enlightenment, ecological science popularization, intangible cultural heritage inheritance, ethnic unity education, and home-school collaborative parenting, spanning the entire learning stage from kindergarten to primary school. This paper systematically elaborates on the practical exploration of Ning’an Korean Ethnic Minority Primary School (including its kindergarten division). Rooted in the local Korean ethnic settlement characteristics, the school has independently developed a full-chain research-based curriculum titled “The Journey of a Grain of Rice,” leveraging local ecological paddy field resources and the provincial-level intangible cultural heritage “Liutou Festival” of Jiangxi Village in Bohai Town. The curriculum comprehensively covers rice seedling cultivation, duck-rice and shrimp-rice ecological farming, paddy field practice, autumn harvesting, rice culture museum study, immersive intangible cultural heritage experiences of the Liutou Festival in Jiangxi Village, and ultimately connects to daily campus dining. On-campus regular activities include parent-child folk workshops for making pine-flavored rice cakes during the Dragon Boat Festival and rice cakes during the Mid-Autumn Festival. The program creates a walking practice classroom beyond traditional walls, embedding parent-child interaction throughout, and connecting five major educational fronts: campus, fields, intangible cultural heritage villages, cultural exhibition halls, and families. The curriculum consistently weaves the sense of community for the Chinese nation throughout the entire process, using rice as a bond and folk customs as a bridge to promote shared labor, shared experiences, and shared enjoyment among children and students of all ethnic groups, thereby constructing an integrated food education system for kindergartens and primary schools. All curriculum plans and activity designs presented in this paper are original creations of the school, providing a localized practical model for county-level ethnic schools seeking integrated education through “food education + intangible cultural heritage + ethnic unity”.